(untitled) (Modern education and development, 2024)
Intensifiers play an important role in linguistics. They are used to strengthen the meaning of a certain word or phrase, to increase its effect. Intensifiers are mostly used with adjectives, verbs, and other words to make their meaning stronger. This article details the typology of intensifiers in English, their types, contexts of use, and linguistic significance.